2019
DOI: 10.3389/fmicb.2019.01265
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fungi Co-occurrence on Mycotoxin Contamination in Maize During the Growing Season

Abstract: Maize is a possible host of many fungi, some of them able to produce different mycotoxins. Few studies exist on co-occurring fungi and resulting multi-mycotoxin contamination in field; for this reason, in field trials were conducted in two consecutive years to verify fungal incidence and mycotoxin production in the case of the co-occurrence of the three main mycotoxigenic fungi of maize in Italy: Aspergillus flavus, Fusarium verticillioides , and Fusarium graminearum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 39 publications
5
47
0
2
Order By: Relevance
“…However, the stress on developing maize-particularly during reproductive phases-facilitates infection by the fungi, mycotoxin production and the contamination of the grain [32]. Moreover, it has been reported that, in the field, fungal metabolism changes in order to adapt to unfavorable environmental conditions or limited nutritional availability [33,34]. These authors highlighted the relevance of studies similar to those presented in this manuscript.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, the stress on developing maize-particularly during reproductive phases-facilitates infection by the fungi, mycotoxin production and the contamination of the grain [32]. Moreover, it has been reported that, in the field, fungal metabolism changes in order to adapt to unfavorable environmental conditions or limited nutritional availability [33,34]. These authors highlighted the relevance of studies similar to those presented in this manuscript.…”
Section: Discussionsupporting
confidence: 53%
“…The presence of A. flavus was much more frequent and occurred at all stages; in comparison to the three Fusarium species detected, which were usually first detected at harvest. It is well-known that A. flavus and F. verticillioides usually co-occur in corn, since they are able to occupy different niches regarding carbon sources [34].…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus and Fusarium are the major fungal genera associated with corn contamination [10]. Indeed, many Aspergillus and Fusarium species are considered common contaminants of food and feed due to their ability to colonize and grow in a wide range of environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures and levels of humidity from silking to maturity stages are favourable conditions for fungal ear colonization by Fusarium species and synthesize of Fusarium mycotoxins (Logrieco et al, 2002), while drier growing seasons suitable for the growth of Aspergillus spp. and aflatoxin accumulation in maize crops (Giorni et al, 2019). The occurrence of mycotoxins in maize grains is also dependent on hybrid susceptibility (Blandino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%